Analysis of temperature and heat partitioning coefficient during friction between polymer and steel. (July 2022) - Xia, Yichun; Yano, Akihiko; Hayashi, Noriyuki; Horaguchi, Norihisa; Xie, Guoxin; Guo, Dan
Abstract: Contact temperature significantly affects the friction and wear performance of polymers. The constant heat partitioning coefficient (constant heat partitioning method) is employed in most friction simulations. In this study, a simulation considering interface temperature continuity was conducted to obtain the contact temperature of the friction between polymer and steel (total heat flux method). The results indicated that the total heat flux method is more consistent with the experiments, and the heat partitioning coefficient is a dynamic parameter during friction. Some factors affecting friction temperature and heat partitioning coefficient were analyzed by experiments and simulations. This study can provide a reference to evaluate the friction temperature between polymer and steel more accurately.